Carbon Nanotube Embedded Polymer Composite: Properties and Applications - Mohanty, Fanismita; K. Swain, Sarat (Current Organic Synthesis, 2017)
Carbon nanotube (CNT) is a promising allotrope of carbon having exceptional mechanical, electrical, thermal and multifunctional properties. Applications of CNTs are increased when it is chosen as an effective filler in polymer composites. The chemical functionalized CNTs are more compatible as reinforcing agent in polymer composites due to its polar nature. This review involves the preparation, characterization and various applications of CNT/polymer composites. Different methods of functionalization of CNTs are discussed and compared with respect to their advantages. The properties of polymers, copolymers and biopolymers based CNT embedded nanocomposites are elaborated. The applications of CNT/polymer nanocomposites are discussed in comparison to reported results.
Keywords: copolymer